Preliminary data on aquatic insects of Dak Mi Protection Forest, Quang Nam province - Ngo Xuan, Nam (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 3DO - 10.25073/2588-1140/vnunst.4518, 2017)
Aquatic insects were investigated from 11 sampling sites in selected waterbodies of Dak Mi Protection Forest in Quang Nam in March, September, 2015 and March, 2016. As the results, a total of 92 species, belonging to 67 genera, 38 families, 8 orders of aquatic insects were recognized here. Among them, the order Ephemeroptera is the most diverse with 26 species (28,26%), followed by the Odonata with 18 species (19,57%), Hemiptera with 13 spieces (14,13%), Tricoptera with 12 species (13,04%). The Coleoptera and Plecoptera have the same diverse with 8 species (8,70%). The Diptera have 6 spieces (6,52%) and the last is Megaloptera has only one species (1,09%). This study has provided the first data of aquatic insects in this area.